3D printing properties and printability definition of Pennahiaargentata surimi and rice starch. (August 2022) - Li, Gaoshang; Zhan, Junqi; Hu, Zhiheng; Huang, Jiayin; Luo, Xunyu; Chen, Jianchu; Yuan, Chunhong; Takaki, Koichi; Hu, Yaqin
Abstract: Correlation of related factors (texture, gel strength, rheological properties) were analyzed for better characterize 3D material printability. Moreover, printability calculation formula also was established to represent material plasticity. Pennahia argentata surimi shown best plasticity with 78% moisture content and 20% rice starch respectively. Additionally, starch and carrageenan increased gel strength, yield stress of surimi and starch respectively, which brought better mechanical strength and supporting ability. They also affected viscosity of surimi (increasing) and starch (decreasing), which brought better fluidity and adhesion respectively, resulting in good printability, especially starch (8%)-surimi, carrageenan (0.5%)-starch. Based on their interaction relationships, 3D printability equation of printing inkswas established their relevance and corresponding unified values. To judge the printability of same materials under different conditions were consistent with real print results. These could provide methods for judging material printability by specific values and promote the application and spread of 3D materials. Graphical abstract: Image 1 Highlights: Plasticity of different materials were shown by printing different shapes. Texture, rheology, gel strength of different materials were determined. Correlation between texture, rheology, gel strength and plasticity was analyzed. Printability equation was established to exhibit materials printability.